Explaining Seemingly Paradoxical Consumer Experiences: Conjoining Weekly Road Rage and Church Attendance - Gau, L.; Woodside, Arch; Martin, D. (Springer, 2013)
© 2013, Springer Science+Business Media New York.The purposes of the current study are threefold: Provide evidence that an extreme paradoxical group exists—people frequently attending church and exhibiting road rage, profile this group, and frame possible explanations for the seemingly paradoxical behaviors. This study employs data from a national (USA) lifestyle survey conducted by Market Facts with 3,350 American respondents. The major questions asked about church participation and road-rage behavior (“giving a finger” and “flashing headlights”). Nomologically, relevant activities include 3 items for church goers and 3 items for road-rage givers. Additionally, 14 items profiled the lifestyles of the unique paradoxical behavior segment. Utilizing cross-tabulation tables, property space analyses identify the double extreme (XX) group (18 people) and other 6 groups with a significant chi-square test, confirming the extreme group exists. Analyses of variance test results show that comparing nomologically relevant activities among the seven groups is all statistically significant, indicating the nomological validity is met. Overall, the XX group tends to have more males, be younger, and have a higher proportion of people working in sales. The profile of lifestyle analyses shows the XX group members have both high ambitions and expectations, might be very frustrated individuals, and equip with the adventurous and masculine traits related to aggression. The XX behavior group’s demographic and psychographic characteristics portray similar lifestyles that differ from other groups. Case-based analyses provide further contextual information of nuances to XX segment individuals. The limited energy theory, the Eagleman’s theory of unconscious mind, and justification theory help to explain why people conjointly go to church and commit road rage. Addressing chronic paradoxical behaviors provides implications for social de-marketing to reduce aggressive anti-social behavior such as road rage. Frequent church attendance may help make people more sensitive to their wrongdoings and gradually revise the anti-social behavior.